Studi Kenabian Muhammad Perspektif Michael Cook - Mohamad Baihaqi Alkawy (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2020)
Muhammad’s prophetic studies have been carried out through various approaches, Michael Cook chose a revisionist approach to seek to explore the history of prophecy through written evidence. In his view, Muhammad’s biography must be examined in more detail based on the evidence obtained to uncover the mystical veils in history. Cook’s criticism of the biographers of Muhammad, made him have to work hard to look at and re-examine the texts of the Quran more closely. This Article will explain the result of Cook’s studies about Muhammad’s success in shifting polytheism to monotheism. In addition, it shows the success of Muhammad as a political actor.